2019
DOI: 10.1073/pnas.1903854116
|View full text |Cite
|
Sign up to set email alerts
|

Long-term in vivo microscopy of CAR T cell dynamics during eradication of CNS lymphoma in mice

Abstract: T cells expressing anti-CD19 chimeric antigen receptors (CARs) demonstrate impressive efficacy in the treatment of systemic B cell malignancies, including B cell lymphoma. However, their effect on primary central nervous system lymphoma (PCNSL) is unknown. Additionally, the detailed cellular dynamics of CAR T cells during their antitumor reaction remain unclear, including their intratumoral infiltration depth, mobility, and persistence. Studying these processes in detail requires repeated intravital imaging of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 55 publications
3
73
0
Order By: Relevance
“…These data support our observation that differences in outcomes in mice treated with ICV and IV delivery reflected differences in capacity for anti-tumor activity promoted by the two routes of delivery. The long-term persistence of memory CAR T cells following ICV administration in absence of antigen, also observed by Mulazzani et al (45), could be due to homeostatic mechanisms driven by factors such as cytokines that are species cross-reactive, such as IL-7 (46,47).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…These data support our observation that differences in outcomes in mice treated with ICV and IV delivery reflected differences in capacity for anti-tumor activity promoted by the two routes of delivery. The long-term persistence of memory CAR T cells following ICV administration in absence of antigen, also observed by Mulazzani et al (45), could be due to homeostatic mechanisms driven by factors such as cytokines that are species cross-reactive, such as IL-7 (46,47).…”
Section: Discussionmentioning
confidence: 52%
“…Absence of GVHD suggests that there is limited engagement of the endogenous TCR in our model and, therefore, xenoreactivity likely does not affect our conclusions. In line with these observations, a recent study by Mulazzani et al (45) showed that intracerebral infusion of CAR T cells exhibits superior anti-tumor efficacy and persistence compared to IV delivery, where…”
Section: Discussionmentioning
confidence: 67%
“…Cranial window implantation was performed as described (27)(28)(29). After anesthesia (intraperitoneal injection of medetomidine, midazolam, and fentanyl) and subcutaneous injection of cefotaxime and dexamethasone, mice were placed on a heating pad (37 • C) and fixed in a modified surgery frame (David Kopf Instruments, USA).…”
Section: Microsurgical Cranial Window Implantationmentioning
confidence: 99%
“…The authors developed a mouse model of orthotopic, fluorescent-labeled PCNSL with intracerebral and periventricular tumor growth and created chronic cranial windows, which allowed longitudinal observation of tumor and T-cell kinetics (4). Three-dimensional quantification of intratumoral T cells by use of two-photon laser scanning microscopy (TPLSM) demonstrated that intravenously administered anti-CD19 CAR T cells accumulated in limited numbers at a late time point, at levels equal to mock CAR T cells, resulting in tumor regression in a fraction of treated mice.…”
Section: Noveltymentioning
confidence: 99%
“…IC, intracerebral; IV, intravenous. This figure includes cropped figures from the article "Long-term in vivo microscopy of CAR T cell dynamics during eradication of CNS lymphoma in mice" by Mulazzani et al (4), under Creative Commons CC-BY-NC-ND 4.0. Permission has been provided by authors of the original work to share modified material.…”
Section: Noveltymentioning
confidence: 99%